Antiviral nanoagents: More attention and effort needed?. (December 2020) - Chen, Yongjiu; Ma, Juan; Xu, Ming; Liu, Sijin
Graphical abstract: Highlights: Engineered nanomaterials have emerging as a tool for the development of next-generation antiviral agents. Antiviral strategies using nanoagents mainly include virus or host cell surface receptor interactions, antiviral agents delivery, and nanovaccines. Future antiviral therapy would require safe, efficient, and broad-spectrum nanoagents. Abstract: The recent COVID-19 outbreak has increasingly engaged researchers in the search for effective antiviral drugs as well as therapeutic treatment options. The shortcomings of existing antiviral agents such as narrow spectrum and low bioavailability, can be overcome through the use of engineered nanomaterials, which, therefore, are considered as a significant next-generation therapeutic option. Thus, the development of novel antiviral nanoagents will certainly help address several future challenges and knowledge gaps.